Lithium ion secondary battery

By using 20%-50%of silicon carbon materials in the negative active coating of lithium ion batteries, and controlling the weight weight gain rate of thermal curve, the problem of conductivity of lithium-ion batteries during circulation is solved. Aviation of high -energy density and excellent circulation performance.

CN119381513APending Publication Date: 2025-01-28ZHUHAI COSMX BATTERY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411543055.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

During the charging and discharging cycle of existing lithium-ion batteries, due to the change in the volume of the silicon-based material, the conductivity of the negative electrode becomes worse, which seriously affects the circulation performance of the lithium-ion batteries.

Method used

Using negative active coatings, containing 20%-50%silicon carbon material, and the weight increase rate of the thermal curve at 600 ° C-800 ° C is within 0.01%-15%, adjust the oxidation reaction of silicon carbon materials Make sure the battery has excellent circulation and expansion performance under the premise of high energy density.

Benefits of technology

Improve the cycle stability and cycle life of lithium ion secondary batteries, ensure high energy density while maintaining excellent circulation and expansion performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381513A_ABST
    Figure CN119381513A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a lithium ion secondary battery which comprises a positive plate and a negative plate, the positive plate comprises a positive current collector and a positive active coating positioned on at least one side surface of the positive current collector; the negative plate comprises a negative current collector and a negative active coating positioned on at least one side surface of the negative current collector; the positive electrode active coating comprises a nickel-cobalt-manganese ternary material; the negative electrode active coating comprises a silicon carbon material; the content of the element Si in the negative electrode active coating is 20%-50%; the thermogravimetric curve of the negative electrode active coating in the air atmosphere has a weight gain peak at the temperature of 600-800 DEG C, and the weight gain rate at the temperature of 600-800 DEG C is 0.01%-15%. The lithium ion secondary battery provided by the invention has high energy density, and also can ensure excellent cycle performance and expansion performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a lithium-ion secondary battery. Background Art

[0002] Lithium-ion batteries have the characteristics of high specific energy, high operating voltage, low self-discharge rate, small size and light weight, and are widely used in the field of consumer electronics. With the rapid development of electric vehicles and mobile electronic devices, people have higher and higher requirements on the energy density, safety, cycle performance and other related aspects of lithium-ion batteries.

[0003] Silicon-based materials have a theoretical gram capacity of up to 4200mAh / g, and their application in lithium-ion batteries has broad prospects. Therefore, the existing technology often uses increasing the doping amount of silicon-based materials in silicon negative electrodes to improve the energy density of lithium-ion batteries. However, during the charge and discharge cycle, as lithium ions are inserted and removed, silicon-based materials will undergo huge volume changes, and as the content of silicon-based materials increases, the volume change of negative electrode silicon-based materials intensifies, causing the negative electrode active material to pulverize and separate from the current collector, resulting in poor conductivity of the negative electrode, which seriously affects the cycle performance of lithium-ion batteries. Summary of the invention

[0004] The purpose of the present invention is to overcome the above problems existing in the prior art and provide a lithium-ion secondary battery having high energy density while still ensuring excellent cycle performance and expansion performance. The specific technical solution is as follows:

[0005] A first aspect of the present invention provides a lithium ion secondary battery, the lithium ion secondary battery comprising a positive electrode sheet and a negative electrode sheet; the positive electrode sheet comprises a positive electrode current collector and a positive electrode active coating located on at least one side of the surface of the positive electrode current collector; the negative electrode sheet comprises a negative electrode current collector and a negative electrode active coating located on at least one side of the surface of the negative electrode current collector;

[0006] The negative electrode active coating comprises a silicon-carbon material; the mass content of element Si in the negative electrode active coating is 20%-50%;

[0007] The thermogravimetric curve of the negative electrode active coating in air atmosphere has a weight gain peak at 600°C-800°C, and the weight gain rate at 600°C-800°C is 0.01%-15%.

[0008] Through the above technical solution, the present invention has at least the following advantages compared with the prior art:

[0009] (1) The negative electrode active coating of the lithium ion secondary battery of the present invention includes silicon-carbon material, and the content of element Si is relatively high, and has high energy density;

[0010] (2) The negative electrode active coating of the lithium ion secondary battery of the present invention has a weight gain peak at 600°C-800°C by controlling the thermogravimetric curve in an air atmosphere, and the weight gain rate at 600°C-800°C is 0.01%-15%, which can ensure that the lithium ion secondary battery has excellent cycle performance and expansion performance while having a high energy density, and can improve the cycle life and cycle stability of the lithium ion secondary battery.

[0011] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 The thermogravimetric curve of the negative electrode active coating in an example of the present invention under air atmosphere is shown.

[0013] Figure 2 Shown is a partial thermogravimetric curve of the negative electrode active coating in an example of the present invention under air atmosphere.

[0014] Figure 3 Shown is a cross-sectional SEM-EDS image of a negative electrode sheet in an example of the present invention.

[0015] Figure 4 Shown is a cross-sectional SEM-EDS image of a positive electrode sheet in an example of the present invention. DETAILED DESCRIPTION

[0016] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0017] The present invention provides a lithium-ion secondary battery, which comprises a positive electrode sheet and a negative electrode sheet; the positive electrode sheet comprises a positive electrode collector and a positive electrode active coating located on at least one side surface of the positive electrode collector; the negative electrode sheet comprises a negative electrode collector and a negative electrode active coating located on at least one side surface of the negative electrode collector.

[0018] In the present invention, the negative electrode active coating may include a silicon-carbon material; the mass content of element Si in the negative electrode active coating may be 20%-50%, for example, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49% or 50%. When the mass content of element Si in the negative electrode active coating is within the above range, it indicates that the content of silicon-carbon material is high, which can make the lithium-ion secondary battery have a higher energy density. The mass content of element Si in the negative electrode active coating in the present invention can be obtained by cross-sectional SEM-EDS test analysis.

[0019] In one example, the mass content of element Si in the negative electrode active coating is 25%-40%.

[0020] In the present invention, the thermogravimetric curve of the negative electrode active coating in an air atmosphere has a weight gain peak at 600°C-800°C, and the thermogravimetric curve of the negative electrode active coating in an air atmosphere has a weight gain rate of 0.01%-15% at 600°C-800°C, for example, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%.

[0021] In yet another example, the weight gain rate at 600° C.-800° C. is 0.3%-8.5%.

[0022] It should be noted that the test method of the thermogravimetric curve of the negative electrode active coating in an air atmosphere is: use a thermogravimetric separator (Waters TA TGA550) to test the negative electrode active coating containing silicon-carbon material, and the test conditions are: a heating rate of 10°C / min in an air atmosphere, a test range of 25°C-1300°C, and finally collect the thermogravimetric data of the negative electrode active layer to obtain a thermogravimetric curve, and record the weight corresponding to the highest point of the weight gain peak within 600°C-800°C as M1, and the weight of the negative electrode active coating corresponding to the starting position of the weight gain peak as M0, and the weight gain rate at 600°C-800°C = (M1-M0) / M0×100%.

[0023] Since the above thermogravimetric curve is the thermogravimetric curve of the negative electrode active coating in air atmosphere, the mass change of the negative electrode active coating material due to oxidation can be observed. The Si element in the silicon-carbon material will be oxidized to SiO by oxygen in the air. x The compound also faces the decomposition of the C element in the negative electrode active coating, which leads to weight loss. The two form a competitive relationship as the temperature gradually increases. Finally, in the temperature range of 600℃-800℃, SiO x The weight gain formed by the compound is greater than the weight loss caused by the oxidative decomposition of the C element represented by the conductive agent and the binder, so there is a weight gain peak at 600℃-800℃.

[0024] The present invention can adjust the amount of Si element that undergoes oxidation reaction in the negative electrode active coating by controlling the weight gain rate of the negative electrode active coating within the range of 0.01%-15% at 600°C-800°C, so that the content of silicon-carbon material that will expand in volume in the negative electrode active coating is effectively controlled. When the content of silicon-carbon material in the negative electrode active coating is too much, the volume expansion of the silicon-carbon material will cause the continuous rupture and regeneration of the SEI film. This process will consume a large amount of active lithium in the electrolyte, increase the internal resistance of the battery, and accelerate the attenuation of the battery capacity; in particular, when the present invention uses a negative electrode active coating material with a high silicon content, due to its greater volume expansion, the damage to the SEI film will also be more serious, and the problem of SEI film instability will be more likely to occur. Therefore, it is necessary to adjust the amount of Si element that undergoes oxidation reaction by controlling the weight gain rate of the negative electrode active coating at 600℃-800℃, so as to avoid the excessive silicon-carbon material from causing serious volume expansion during the lithium insertion process, reduce the rupture frequency of the SEI film, reduce the consumption of active lithium and electrolyte, and thus improve the cycle expansion performance of the negative electrode sheet, and improve the cycle stability and cycle life of the lithium ion secondary battery. When the content of silicon-carbon material in the negative electrode active coating is too small, the gram capacity of the negative electrode active material is low, which will affect the energy density of the battery and does not meet the current application requirements for lithium ion secondary batteries. The present invention can increase the amount of Si element that undergoes oxidation reaction by controlling the weight gain rate of the negative electrode active coating at 600℃-800℃, thereby avoiding the decrease in the energy density of the lithium ion secondary battery. Therefore, the lithium ion secondary battery of the present invention can have excellent cycle performance and expansion performance while having high energy density, and has a long cycle life and excellent cycle stability.

[0025] In addition, since the weight gain rate can also reflect the weight loss of the C element, the present invention controls the weight gain rate of the negative electrode active coating within the range of 0.01% - 15% at 600°C - 800°C, which helps to improve the bonding strength and electrical conductivity between the silicon-carbon material particles in the negative electrode active coating, thereby constructing a more stable silicon-carbon material conductive network, enhancing the electrical conductivity of the negative electrode active coating, increasing the lithium ion transmission rate, and further improving the decline in electrical performance of the lithium ion secondary battery caused by the high content of silicon-carbon material; moreover, the bonding strength between the silicon-carbon material particles is effectively improved, which also helps to reduce the cyclic expansion problem of the negative electrode active coating in the later stage of cycling, and further improves the cycle life and cycle stability of the lithium ion secondary battery.

[0026] In the present invention, the positive electrode active coating includes a nickel-cobalt-manganese ternary material, and the nickel-cobalt-manganese ternary material includes a substance with the chemical formula Li a Ni x Co y Mn z M k O2, where 0.9 ≤ a ≤ 1.1 (such as 0.9, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1, 1.05 or 1.1), 0.8 ≤ x ≤ 0.95 (such as 0.8, 0.85, 0.9, 0.91, 0.92, 0.93, 0.94 or 0.95), 0 < y ≤ 0.2 (such as 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19 or 0.2), 0 < z ≤ 0.2 (such as 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19 or 0.2), 0 ≤ k ≤ 0.05 (such as 0.01, 0.02, 0.03, 0.04 or 0.05), and M is selected from at least one of Al, Zr, B, Y, Sr, W, Mg, Fe, Ti and Nb.

[0027] In one example, 0.9 ≤ x ≤ 0.95.

[0028] The negative electrode active coating with high silicon content has high specific capacity, but its first coulomb efficiency is low, which greatly consumes the number of electrochemically active lithium ions in the battery system, thereby reducing the energy density of the whole battery. The present invention uses a high-nickel ternary positive electrode material in the positive electrode active coating, which has a higher gram capacity, and the battery per unit weight can store more electrical energy. With a high-silicon content negative electrode, it can compensate for the consumed electrochemically active lithium ions in the battery system, solving the problem of high silicon content negative electrode active lithium consumption. Moreover, the high silicon content negative electrode limits the proportion of silicon-carbon materials used alone in the battery due to its own volume expansion problem, but the high-nickel ternary positive electrode material can make up for this deficiency to a certain extent for the improvement of the battery gram capacity, and cooperates with the high silicon content negative electrode to keep the energy density of the overall battery at a high level. In addition, the use of a high silicon content negative electrode and a high nickel ternary positive electrode material can also help improve the cycle stability of the whole battery system, thereby improving the cycle retention rate of the whole battery.

[0029] Further, the negative electrode active coating containing silicon-carbon material is tested by using a thermogravimetric separator (Waters TATGA550) using the above-mentioned thermogravimetric curve test method to obtain a thermogravimetric curve, and the weight at the test end point of 900°C in the temperature range of 800°C-1200°C is recorded as M2, the weight of the original negative electrode active coating is recorded as M, and the residual amount at 800°C-1200°C = M2 / M×100%. In the present invention, the thermogravimetric curve of the negative electrode active coating in air atmosphere has a residual amount of 60%-95% at 800°C-1200°C, for example, 60%, 61%, 63%, 65%, 67%, 69%, 70%, 72%, 74%, 75%, 76%, 78%, 80%, 81%, 83%, 85%, 87%, 89%, 90%, 91%, 93%, 95%, and is oxidized to SiO x The silicon-carbon material of the compound forms part of the residual amount, and the oxidation decomposition of the C element represented by the conductive agent and the binder constitutes the main part of the weight loss. Therefore, by controlling the residual amount of the negative electrode active coating at 800℃-1200℃ within the range of 60%-95%, the decomposition weight loss of the C element can be further adjusted, which helps to further improve the bonding strength between the silicon-carbon material particles and improve the expansion problem of the negative electrode active coating. In addition, by adjusting the decomposition weight loss of the C element, it helps to improve the conductive properties of the negative electrode active coating and build a more stable conductive network, thereby further improving the cycle life and cycle stability of the lithium-ion secondary battery. And because part of the residual amount is SiO xCompound, so controlling the residual amount of the negative electrode active coating can also ensure that the active coating of the negative electrode sheet has a higher content of Si element, so that the lithium ion secondary battery of the present invention can have a higher energy density while having excellent cycle performance and expansion performance.

[0030] In one example, the thermogravimetric curve of the negative electrode active coating in air atmosphere shows that the residual amount at 800° C.-1200° C. is 80%-95%.

[0031] In summary, by simultaneously controlling the thermogravimetric curve of the negative electrode active coating in an air atmosphere, the weight gain rate at 600°C-800°C is 0.01%-15%, and the residual amount at 800°C-1200°C is 60%-95%, which can match the appropriate Si element content and C element content, so that the lithium-ion secondary battery can have excellent cycle performance and expansion performance while ensuring the high energy density of lithium ions.

[0032] In the present invention, the mass content of element Ni in the positive electrode active coating can be 35%-70%, for example, 35%, 36%, 37%, 37.7%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 52%, 54.3%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69% or 70%. During the electrochemical cycle of high-nickel ternary positive electrode materials, side reactions occur on the surface and their crystal structure is unstable, so their capacity will decay as the cycle progresses. By further adjusting the mass content of element Ni in the positive electrode active coating within the above range, it is possible to ensure that the positive electrode active material has a high gram capacity while avoiding structural instability; moreover, when a suitable mass content of element Ni is used in combination with a high-silicon content negative electrode, it helps to compensate for the lithium ion loss of the negative electrode silicon-carbon material in the electrochemical process, solving the problem of high active lithium consumption in high-silicon content negative electrodes. By working in synergy with the high-silicon content negative electrode, the full battery can achieve high energy density. At the same time, when the high-silicon content negative electrode is used in combination with a positive electrode containing a suitable content, it can also avoid excessive element Ni and cause a decrease in the cycle stability of the positive electrode active material. In addition, the element Ni with a suitable mass content in the positive electrode active coating can, to a certain extent, make up for the single application ratio of the element Si in the negative electrode active coating limited by its own volume expansion problem, so that the negative electrode active coating of the present invention can remain unchanged in the weight gain range of 600°C-800°C, thereby ensuring the high silicon content of the negative electrode sheet and the high energy density of the lithium-ion secondary battery.

[0033] The mass content of element Ni in the positive electrode active coating in the present invention can be obtained by cross-sectional SEM-EDS test analysis.

[0034] In one example, the mass content of element Ni in the positive electrode active coating is 35%-60%.

[0035] In one example, the ratio of the mass content of the element Ni in the positive electrode active coating to the mass content of the element Si in the negative electrode active coating is a, and a is 1-4, for example, 1, 1.5, 2, 2.5, 3, 3.5 or 4. Too much mass content of the element Si in the negative electrode active coating will lead to a reduction in the number of electrochemically active lithium ions in the battery system, and too little mass content will lead to a decrease in the specific capacity of the negative electrode. Too much mass content of the element Ni in the positive electrode active coating will lead to a decrease in the stability of the crystal structure, and too little mass content will lead to an inability to better compensate for the lithium ion loss of the negative electrode silicon-carbon material in the electrochemical process. Therefore, the present invention can better match the appropriate content of the element Ni and the element Si by further controlling the content ratio of the two elements, avoid reducing the energy density of the whole battery system, and can simultaneously improve the volume expansion of the negative electrode and the cycle stability of the positive electrode, thereby improving the overall cycle performance of the whole battery.

[0036] In one example, a is 1-2.

[0037] In the present invention, the ratio of the surface density of the positive electrode active coating to the surface density of the negative electrode active coating is b, and b is 5.5-15, for example, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10, 10.5, 11, 11.5, 12, 12.5, 13, 13.5, 14.5 or 15. A reasonable positive and negative electrode surface density ratio is helpful to improve the cycle stability of the battery, especially the negative electrode active coating with a high silicon content. By controlling the ratio b of the surface density of the positive electrode active coating to the surface density of the negative electrode active coating within the above range, the precipitation of lithium ions on the negative electrode side with a high silicon content can be avoided, thereby extending the cycle life of the lithium-ion secondary battery. Moreover, when the positive electrode active coating includes a nickel-cobalt-manganese ternary material, by controlling the ratio b of the surface density of the positive electrode active coating to the surface density of the negative electrode active coating, it is also helpful to maintain the stability of the positive electrode structure of the ternary material, avoid the difficulty of lithium ion insertion / ejection caused by excessively high surface density, thereby enabling the lithium-ion secondary battery to maintain good performance during the cycle process and extending the cycle life of the lithium-ion secondary battery.

[0038] In one example, b is 6-10.

[0039] In the present invention, a and b satisfy: 8≤a×b≤16, for example, a=1.8, b=6, a×b=10.8, a=1.6, b=7, a×b=11.2, a=1.2, b=9.5, a×b=11.4. In the present invention, a and b are inversely proportional. When a becomes larger, that is, the content of element Ni in the positive electrode active coating is relatively large, and the content of element Si in the negative electrode active coating is relatively small, b needs to be relatively reduced, that is, the surface density of the positive electrode active coating is reduced, and the surface density of the negative electrode active coating is increased. The advantage of this is to reduce battery polarization, improve discharge rate performance, and achieve high-power discharge performance; at the same time, when a becomes smaller, b needs to be relatively increased. The advantage of this is to reduce battery weight and achieve higher mass energy density. In summary, the two are combined with each other. When a and b are in a suitable range, the high-nickel ternary material positive electrode and the high-silicon content negative electrode can be better coordinated. When they are used in conjunction with each other, the lithium-ion secondary battery can achieve better power performance and higher mass energy density.

[0040] In one example, 10≤a×b≤14.

[0041] In the present invention, the electrical conductivity of the silicon-carbon material can be 0.01S / cm-30S / cm, for example, 0.01S / cm, 0.02S / cm, 0.03S / cm, 0.04S / cm, 0.05S / cm, 0.06S / cm, 0.07S / cm, 0.08S / cm, 0.09S / cm, 0.1S / cm, 0.2S / cm, 0.3S / cm, 0.4S / cm, 0.5S / cm, 1S / cm, 2S / cm, 3S / cm, 4S / cm, 5S / cm, 10S / cm, 15S / cm, 20S / cm, 25S / cm, 30S / cm. By optimizing the electrical conductivity of the silicon-carbon material, the specific capacity and energy density of the battery can be improved, because good electrical conductivity helps to more efficiently improve the theoretical lithium insertion capacity of silicon.

[0042] In one example, the electrical conductivity of the silicon carbon material is 10 S / cm-30 S / cm.

[0043] In the present invention, the average particle size of the silicon-carbon material can be 1 μm-20 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm. Appropriate control of the average particle size of the silicon-carbon material can also avoid the volume change of the negative electrode during the charge and discharge cycle, thereby reducing the generation of stress and cracks, improving the cycle stability of the negative electrode active coating, and increasing the cycle life of the lithium-ion secondary battery. In addition, the average particle size of the silicon-carbon material can be obtained by taking the average value after testing with a particle size tester. The test method is: using Malvern MS3000, setting the test conditions as follows: refractive index 2.1, absorptivity 1.0, shading 8-12%, water (or ethanol) as the dispersant, stirring rate 2500rpm, and testing 3 times to obtain the average value, where the D50 value is the average particle size of the silicon-carbon particles.

[0044] In one example, the average particle size of the silicon-carbon material is 5 μm-15 μm.

[0045] In the present invention, based on the total mass of the negative electrode active coating, the mass content of the silicon-carbon material is 60%-95%, for example, 60%, 70%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 93.1%, 94% or 95%.

[0046] In one example, based on the total mass of the negative electrode active coating, the mass content of the silicon-carbon material is 90%-95%.

[0047] In the present invention, the mass content of element Si in the silicon-carbon material is 20%-70%, for example, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65% or 70%.

[0048] In one example, the mass content of element Si in the silicon-carbon material is 30%-60%.

[0049] In the present invention, the negative electrode active coating further comprises a negative electrode binder, and the negative electrode binder comprises at least one of polyacrylate, polyamide, polyimide, polyamideimide, polyvinylidene fluoride, styrene-butadiene rubber, sodium alginate, polyvinyl alcohol, polytetrafluoroethylene, polyacrylonitrile, sodium carboxymethyl cellulose and potassium carboxymethyl cellulose.

[0050] In the present invention, the negative electrode active coating also includes a negative electrode conductive agent, and the negative electrode conductive agent includes carbon black and single-walled carbon nanotubes. When carbon black and single-walled carbon nanotubes are used together as negative electrode conductive agents, they help to form a conductive network, avoid the influence of the cyclic volume expansion of the silicon-carbon material, and can also improve the conductivity of the silicon-carbon material.

[0051] In one example, the aspect ratio of the single-walled carbon nanotube is greater than or equal to 500. Since the negative electrode with a high silicon content is prone to volume expansion problems during the lithium insertion process, when the aspect ratio of the single-walled carbon nanotube in the negative electrode conductive agent is greater than or equal to 500, it is more conducive to stabilizing the formation of a conductive network in the negative electrode active coating, because when the silicon content of the negative electrode is high, the contact between the silicon-carbon material particles is relatively large, and the negative electrode conductive agent uses single-walled carbon nanotubes with a high aspect ratio, which is more conducive to winding the silicon-carbon material particles and strengthening the network bonding between the silicon-carbon material particles, thereby improving the conductivity of the silicon-carbon material during the cycle, and providing a certain buffer space for the silicon-carbon material particles, and also helping to alleviate the cyclic expansion of the silicon-carbon material, thereby further improving the cycle life and selective cycle stability of the lithium-ion secondary battery.

[0052] In one example, the mass content of the single-walled carbon nanotubes in the negative electrode conductive agent is 60%-80%, for example, 60%, 65%, 70%, 75%, or 80%.

[0053] In the present invention, the silicon-carbon material comprises a porous carbon matrix and silicon dispersed in the pores of the porous carbon matrix. The silicon-carbon material with the above special structure can better alleviate the volume change of silicon particles and improve the cycle performance and expansion performance of the battery.

[0054] In one example, the silicon-carbon material further includes a carbon coating layer on the surface, and the carbon coating layer enables the silicon-carbon material to further maintain structural stability during repeated expansion and contraction of Si.

[0055] In the present invention, the porosity of the negative electrode sheet may be 10%-60%, for example, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, or 60%.

[0056] In one example, the porosity of the negative electrode sheet is 25%-35%.

[0057] In the present invention, the surface resistance of the negative electrode sheet can be 2Ω·cm-20Ω·cm, for example, 2Ω·cm, 3Ω·cm, 4Ω·cm, 5Ω·cm, 6Ω·cm, 7Ω·cm, 8Ω·cm, 9Ω·cm, 10Ω·cm, 11Ω·cm, 12Ω·cm, 13Ω·cm, 14Ω·cm, 15Ω·cm, 16Ω·cm, 17Ω·cm, 18Ω·cm, 19Ω·cm, and 20Ω·cm.

[0058] In one example, the surface resistivity of the negative electrode sheet is 5Ω·cm-15Ω·cm.

[0059] The present invention can increase the content of active materials per unit area by further optimizing the surface density of the negative electrode sheet, thereby improving the energy density of the battery; secondly, reasonable porosity design can improve the wettability of the electrolyte and reduce the migration impedance of lithium ions in the negative electrode, thereby further improving the charge and discharge rate and cycle performance of the battery.

[0060] In the present invention, the negative electrode active coating may further include a carbon-based material, and based on the total mass of the negative electrode active coating, the mass content of the carbon-based material is 0% to 20%, for example, 0%, 5%, 10%, 15% or 20%.

[0061] In one example, based on the total mass of the negative electrode active coating, the mass content of the carbon-based material is 0% to 10%.

[0062] In one example, the carbon-based material includes at least one of natural graphite, artificial graphite, or mesocarbon microbeads.

[0063] In the present invention, based on the total mass of the negative electrode active coating, the mass content of the negative electrode conductive agent is 2%-10%, for example, 2%, 2.5%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%.

[0064] In one example, based on the total mass of the negative electrode active coating, the mass content of the negative electrode conductive agent is 4%-8%.

[0065] In the present invention, based on the total mass of the negative electrode active coating, the mass content of the negative electrode binder is 2%-10%, for example, 2%, 2.5%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%.

[0066] In one example, based on the total mass of the negative electrode active coating, the mass content of the negative electrode binder is 4%-8%.

[0067] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0068] In the following examples, unless otherwise specified, all materials used were commercially available analytical grade.

[0069] The following examples serve to illustrate the present invention.

[0070] Example 1

[0071] Prepare as follows:

[0072] Preparation of negative electrode:

[0073] The negative electrode active material silicon carbon material (average conductivity of 15S / cm, average particle size of 8μm, element Si content of 40%), sodium carboxymethyl cellulose, polyacrylic acid, styrene-butadiene rubber, Super-P, and single-walled carbon nanotubes were mixed in a mass ratio of 90:1:2:2:1.5:3.5, and an appropriate amount of water was added as a solvent. After being stirred evenly by a vacuum mixer, the slurry was evenly coated on the surface of a high-strength carbon-coated copper foil with a thickness of 6μm. The single-sided surface density of the coated negative electrode active coating was 2.2mg / cm 2 The coated electrode was transferred to a vacuum drying oven and baked at 85°C for 12 hours. The electrode was rolled and sliced ​​by a double-roller press to obtain the negative electrode. The cross-sectional SEM-EDS image of the negative electrode is shown in FIG. Figure 3 As shown in the figure, the result is the mass content of element Si in the negative electrode sheet (including the weight of the negative electrode collector). By calculation, it can be obtained that the content of element Si in the negative electrode active coating is 27%; in addition, the porosity of the negative electrode sheet is 30% and the surface resistance of the negative electrode sheet is 11Ω·cm.

[0074] Preparation of positive electrode:

[0075] Lithium nickel cobalt manganese oxide (NCM955, LiNi 0.89 Co 0.05 Mn 0.05 Al 0.01 O2, at this time, the proportion of Ni in the nickel-cobalt-manganese ternary material is x = 0.9), polyvinylidene fluoride (PVDF), acetylene black and single-walled carbon nanotubes (CNT) are mixed in a mass ratio of 97.4:1.2:0.5:0.9, and solvent N-methylpyrrolidone is added to obtain positive electrode slurry through a vacuum mixer. The positive electrode slurry is evenly coated on a high-strength aluminum foil with a thickness of 9μm, and the surface density of the coating is 15.3mg / cm2 The aluminum foil coated with the positive electrode slurry was dried in a forced air drying oven at 60°C for 5 minutes for preliminary drying, and then baked in a vacuum oven at 100°C for 10 hours. The positive electrode sheet was rolled and sliced ​​by a roller press to obtain the positive electrode sheet. The cross-sectional SEM-EDS image of the positive electrode sheet is as follows: Figure 4 As shown in the figure, the result shown in the figure is the mass content of element Ni in the positive electrode sheet (including the weight of the positive electrode current collector). Through calculation, it can be obtained that the content of element Ni in the positive electrode active coating is 43.5%.

[0076] Preparation of lithium-ion secondary batteries:

[0077] The negative electrode sheet and the positive electrode sheet obtained in the above steps, and the commercially available separator are stacked in the order of the positive electrode sheet, the separator and the negative electrode sheet, and then wound to obtain a battery cell; the battery cell is placed in an outer packaging aluminum foil, and the commercially available electrolyte is injected into the outer packaging, and a lithium ion secondary battery is obtained through vacuum packaging, standing, forming, shaping, sorting and other processes. The battery of the present invention has a charge and discharge range of 2.5-4.35V.

[0078] See Table 1 and Table 2 for details, denoted as A1.

[0079] Embodiments 2 to 8

[0080] Examples 2 to 8 are carried out with reference to Example 1, with the only difference being that the content of silicon-carbon material in the negative electrode active coating and the content of conductive agent in the negative electrode active coating are changed, see Table 1 and Table 2 for details, and Examples 2 to 8 are sequentially recorded as A2-A8.

[0081] Embodiments 9-10

[0082] Examples 9 to 10 are carried out with reference to Example 1, with the only difference being that the contents of silicon-carbon material, negative electrode conductive agent and negative electrode binder in the negative electrode active coating are changed, and the content of element Si in the silicon-carbon material is changed, see Table 1 and Table 2 for details.

[0083] Examples 11-12

[0084] Examples 11 to 12 were carried out with reference to Example 1, with the only difference being that the content of the silicon-carbon material in the negative electrode active coating and the content of the carbon-based material in the negative electrode active coating were changed, see Table 1 and Table 2 for details.

[0085] Embodiments 13-14

[0086] Examples 13 to 14 are carried out with reference to Example 1, with the only difference being that the content of silicon-carbon material in the negative electrode active coating, the content of carbon-based material in the negative electrode active coating and the content of element Si in the silicon-carbon material are changed, see Tables 1 and 2 for details.

[0087] Embodiments 15 to 17

[0088] Examples 15 to 17 are carried out with reference to Example 1, with the only difference being that the specific materials used in the nickel-cobalt-manganese ternary material are changed, resulting in a change in the nickel proportion x in the nickel-cobalt-manganese ternary material:

[0089] Example 15, nickel cobalt manganese oxide is selected from LiNi 0.95 Co 0.02 Mn 0.02 Mg 0.01 O2, at this time, the proportion of the element Ni in the nickel-cobalt-manganese ternary material is x=0.95, see Table 1 and Table 2 for details;

[0090] Example 16, nickel cobalt manganese oxide is selected from LiNi 0.8 Co 0.1 Mn 0.1 O2, at this time, the proportion of the element Ni in the nickel-cobalt-manganese ternary material is x=0.8, see Table 1 and Table 2 for details;

[0091] Example 17, LiNi cobalt manganese oxide is selected from LiNi 0.6 Co 0.2 Mn 0.15 Fe 0.05 O2, at this time, the proportion of element Ni in the nickel-cobalt-manganese ternary material is x=0.6, see Table 1 and Table 2 for details.

[0092] Embodiments 18 to 19

[0093] Examples 18 to 19 were carried out with reference to Example 1, with the only difference being that the conductivity and average particle size of the silicon-carbon material were changed, as shown in Tables 1 and 2 for details.

[0094] Embodiment 20-21

[0095] Example 20 was carried out with reference to Example 1, with the only difference being that the compaction density of the negative electrode active coating was changed, so that the porosity and surface resistance of the negative electrode sheet were changed, as shown in Tables 1 and 2 for details.

[0096] Example 21 was carried out with reference to Example 1, with the only difference being that the content of the negative electrode binder in the negative electrode active coating was changed, so that the porosity and surface resistance of the negative electrode sheet were changed, as shown in Tables 1 and 2 for details.

[0097] Comparative Examples 1-2

[0098] Comparative Examples 1 to 2 were carried out with reference to Example 1, with the only difference being that the content of silicon-carbon material in the negative electrode active coating and the content of carbon-based material in the negative electrode active coating were changed, see Table 1 and Table 2 for details, and Comparative Examples 1 to 2 are sequentially recorded as A9-A10.

[0099] Comparative Example 3

[0100] Comparative Example 3 was carried out with reference to Example 1, with the only difference being that the content of silicon-carbon material in the negative electrode active coating and the content of carbon-based material in the negative electrode active coating were changed, as shown in Table 1 and Table 2 for details.

[0101] Comparative Example 4

[0102] Comparative Example 4 was carried out with reference to Example 1, with the only difference being that the contents of silicon-carbon material, negative electrode conductive agent and negative electrode binder in the negative electrode active coating were changed, and the content of element Si in the silicon-carbon material was changed, see Table 1 and Table 2 for details.

[0103] Table 1

[0104]

[0105]

[0106] In Table 1, since no silicon-carbon material is added to the negative electrode active coating in Comparative Example 2, the content of Si in the silicon-carbon material, the conductivity and the average particle size of the silicon-carbon material are represented by “ / ”.

[0107] Table 2

[0108]

[0109] In Table 2, in Comparative Example 2, since the content of element Si in the negative electrode active coating is 0, the ratio a of the content of element Ni in the positive electrode active coating to the content of element Si in the negative electrode active coating cannot be calculated, so it is represented by “ / ”.

[0110] Negative electrode test example

[0111] Test the thermogravimetric curve of the negative electrode sheet. The test steps are as follows:

[0112] S8: Separate the current collector and the negative electrode active layer of the negative electrode sheet and collect the negative electrode active coating layer.

[0113] S9: Place the negative electrode active coating layer material into a thermogravimetric analyzer, heat the material in an air atmosphere through a programmed temperature control system, measure the mass change of the material through a detection system, and record the relationship between the mass change and temperature or time through a recording system.

[0114] S10: Collect thermogravimetric data of the negative electrode active layer, obtain a thermogravimetric curve, calculate the weight gain rate of the negative electrode active layer at 600°C-800°C and the residual amount at 800°C-1200°C in an air atmosphere, and record them in Table 3.

[0115] Table 3

[0116]

[0117] In Table 3, since the mass content of silicon-carbon material in the negative electrode active coating is too small in Comparative Examples 1 and 2, there is no weight gain in the range of 600°C-800°C of the thermogravimetric curve under air atmosphere, and the weight gain rate cannot be calculated, so it is represented by " / "; in Comparative Example 2, the negative electrode active coating does not contain silicon-carbon material, but only contains carbon-based material, so the residual amount at 800°C-1200°C is 0%.

[0118] Lithium-ion secondary battery test example

[0119] Mass energy density test:

[0120] En (discharge energy) = R1 (discharge capacity of the first cycle) * V1 (average discharge voltage of the first cycle), energy density weight WED = En / W (Wh / Kg), W is the mass of the battery cell after secondary sealing, and the test results are recorded in Table 4.

[0121] 25℃ Cyclic Performance Test:

[0122] The battery cell to be tested was transferred to a constant temperature room at 25±1℃ and allowed to stand for 30min. It was charged to 4.3V at a constant current of 1.8C (11700mAh). It was charged to a charging current of less than 0.05C (325mAh) at a constant voltage of 4.3V and allowed to stand for 10min. The thickness of the battery cell tested by a thickness gauge was Qx (X=number of cycles, 800T). It was discharged to 2.5V at a constant current of 4C (26000mAh) and allowed to stand for 10min. The above test was a complete cycle process. The discharge capacity (mAh) was recorded as Rx (X=number of cycles), and the capacity retention rate was Ux=Rx / R1*100%. The test results are recorded in Table 4.

[0123] 25℃ Cyclic Expansion Test:

[0124] The battery cell is charged to 3.8V at a constant current of 1.8C, and then charged to a constant voltage of 3.8V until the charging current is less than 0.05C. It is left to stand for 10 minutes. At this time, the battery cell is in a 50% SOC state. The weight of the battery cell measured by the mass measuring instrument is W Kg, and the thickness of the battery cell measured by the thickness measuring machine is Q0 mm. The cycle expansion rate of the battery cell is L x =Q x / Q0*100%, the test results are recorded in Table 4.

[0125] Table 4

[0126]

[0127]

[0128] Figure 1 The thermogravimetric curves of the negative electrode active coatings prepared in Examples 1-8 and Comparative Examples 1-2 of the present invention under air atmosphere are shown in FIG. Figure 2 It is a partial graph of the thermogravimetric curves of the negative electrode active coating of Examples 1-8 of the present invention and Comparative Examples 1-2 in air atmosphere.

[0129] It can be seen from Examples 1-8 and Comparative Examples 1-2 that as the mass content of the silicon-carbon material in the negative electrode active coating changes, the weight gain rate of the negative electrode active coating at 600°C-800°C in an air atmosphere changes, with the weight gain rate of A1 being 3%, the weight gain rate of A2 being 5.5%, the weight gain rate of A3 being 5%, the weight gain rate of A4 being 0.8%, the weight gain rate of A6 being 0.3%, the weight gain rate of A7 being 8.4%, the weight gain rate of A8 being 7.9%, and A9 and A10 not gaining weight within the temperature range of 600°C-800°C; combined with the data in Table 4, it can be seen that in Comparative Examples 1 and 2, since the mass content of the silicon-carbon material in the negative electrode active coating is low and the content of the carbon-based material is relatively high, and the volume change of the carbon-based material is smaller than that of the silicon-carbon material, the negative electrode sheet in the later stage of the cycle will show a smaller volume expansion, and therefore, the cycle capacity of the lithium-ion secondary battery of Comparative Examples 1 and 2 is The retention rate and expansion rate are relatively better than the cycle capacity retention rate and expansion rate of Example 1, but the greater the proportion of carbon-based materials in the negative electrode active coating, the smaller the gram capacity of the negative electrode active material will be, so it will seriously affect the unit mass lithium ion storage capacity of the lithium ion secondary batteries of Comparative Examples 1 and Comparative Examples 2, resulting in a sharp drop in the mass energy density of the lithium ion battery, which does not meet the application requirements; while the present invention controls the weight gain rate of the negative electrode active coating at 600°C-800°C within the range of 0.01%-15%, the mass energy density, capacity retention rate and expansion rate of the lithium ion secondary battery can be significantly improved and enhanced. Compared with Comparative Examples 1-2, the lithium ion secondary batteries A1-A8 prepared in Examples 1-8 have higher mass energy density, and the cycle performance and expansion performance of the lithium ion secondary batteries are also significantly improved, indicating that the lithium ion secondary battery of the present invention has excellent cycle life and cycle stability.

[0130] Compared with Example 1, in Comparative Example 4, the mass content of element Si in the negative electrode active coating is too high, and the weight gain rate of the negative electrode active coating at 600°C-800°C exceeds 15%, so the mass energy density of the lithium ion secondary battery of Comparative Example 4 will be higher than that of Example 1, but the higher the mass content of element Si in the negative electrode active coating, the greater the volume change of the negative electrode sheet will be, causing the negative electrode active material to be pulverized and separated from the current collector, thereby causing the negative electrode conductivity to deteriorate, seriously affecting the cycle performance of the lithium ion battery, so the capacity retention rate and expansion rate in the later cycle of Comparative Example 4 are much worse than those of Example 1, and it cannot be guaranteed that the lithium ion secondary battery maintains excellent cycle performance and expansion performance while having a high energy density.

[0131] Compared with Example 1, Example 9 has a lower mass content of element Si in the negative electrode active coating, so the mass energy density is smaller than that of Example 1. In addition, due to the presence of high-nickel ternary materials in the positive electrode active coating, the capacity will decay in the later stage of the cycle. Therefore, compared with Example 1, the cycle capacity retention rate and expansion rate of Example 9 are slightly worse than those of Example 1. Therefore, it is necessary to appropriately increase the element Si content in the negative electrode active coating to ensure high energy density while having excellent cycle performance and expansion performance.

[0132] Compared with Example 1, Example 10 has an increased mass content of element Si in the negative electrode active coating, so the mass energy density is greater than that of Example 1, but the cycle performance and expansion performance will be relatively reduced due to the volume expansion of the negative electrode in the later stage of the electrochemical cycle, so the cycle capacity retention rate and cycle expansion rate of Example 10 are reduced.

[0133] Compared with Example 1, the mass content of silicon-carbon material in the negative electrode active coating is reduced, and the content of carbon-based material in the negative electrode active coating is increased, resulting in a decrease in the mass content of element Si in the negative electrode active coating. Therefore, the mass energy density of Example 11 decreases, and because the proportion of single-walled carbon nanotubes in the negative electrode conductive agent is adjusted, the cycle expansion is large and the cycle performance decays quickly.

[0134] In Example 16, compared with Example 1, the mass content of element Ni in the positive electrode active coating is reduced, so the cycle retention rate of the lithium-ion secondary battery will be better, but the mass content of element Ni in the positive electrode active coating is low, which will lead to increased lithium ion loss in the high silicon content negative electrode during the electrochemical process, thereby affecting the mass energy density of the lithium-ion secondary battery. Therefore, compared with Example 1, the mass energy density of Example 16 is reduced, but since the proportion of single-walled carbon nanotubes in the negative electrode conductive agent is appropriately increased, the cycle expansion performance of the lithium-ion secondary battery is better.

[0135] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A lithium ion secondary battery, characterized in that: The lithium-ion secondary battery comprises a positive electrode sheet and a negative electrode sheet; the positive electrode sheet comprises a positive electrode current collector and a positive electrode active coating located on at least one side of the surface of the positive electrode current collector; the negative electrode sheet comprises a negative electrode current collector and a negative electrode active coating located on at least one side of the surface of the negative electrode current collector; The negative electrode active coating comprises a silicon-carbon material; the mass content of element Si in the negative electrode active coating is 20%-50%; The thermogravimetric curve of the negative electrode active coating in air atmosphere has a weight gain peak at 600°C-800°C, and the weight gain rate at 600°C-800°C is 0.01%-15%.

2. The lithium ion secondary battery according to claim 1, wherein The positive electrode active coating includes a nickel-cobalt-manganese ternary material, and the nickel-cobalt-manganese ternary material includes a substance with the chemical formula Li a Ni x Co y Mn z M k O2, where 0.9 ≤ a ≤ 1.1, 0.8 ≤ x ≤ 0.95, 0 < y ≤ 0.2, 0 < z ≤ 0.2, 0 ≤ k ≤ 0.05, and M is selected from at least one of Al, Zr, B, Y, Sr, W, Mg, Fe, Ti, and Nb; preferably, 0.9 ≤ x ≤ 0.

95.

3. The lithium ion secondary battery according to claim 1, wherein The mass content of element Si in the negative electrode active coating is 25%-40%; And / or, the thermogravimetric curve of the negative electrode active coating in air atmosphere has a weight gain rate of 0.3%-8.5% at 600° C.-800° C.

4. The lithium ion secondary battery according to claim 1, wherein The thermogravimetric curve of the negative electrode active coating in air atmosphere shows that the residual amount at 800° C.-1200° C. is 60%-95%, preferably 80%-95%.

5. The lithium ion secondary battery according to any one of claims 1 to 4, wherein: The mass content of element Ni in the positive electrode active coating is 35%-70%, preferably 35%-60%; Preferably, the ratio of the mass content of the element Ni in the positive electrode active coating to the mass content of the element Si in the negative electrode active coating is a, and a is 1-4.

6. The lithium ion secondary battery according to claim 5, wherein: The ratio of the surface density of the positive electrode active coating to the surface density of the negative electrode active coating is b, and b is 5.5-15, preferably 6-10; Preferably, a and b satisfy: 8≤a×b≤16; More preferably, 10≤a×b≤14.

7. The lithium ion secondary battery according to any one of claims 1 to 4, wherein: The electrical conductivity of the silicon-carbon material is 0.01S / cm-30S / cm; preferably 10S / cm-30S / cm; And / or, the average particle size of the silicon-carbon material is 1 μm-20 μm; preferably 5 μm-15 μm; And / or, based on the total mass of the negative electrode active coating, the mass content of the silicon-carbon material is 60%-95%; preferably 90%-95%; And / or, the mass content of element Si in the silicon-carbon material is 20%-70%, preferably 30%-60%.

8. The lithium ion secondary battery according to any one of claims 1 to 4, wherein: The negative electrode active coating further comprises a negative electrode binder, wherein the negative electrode binder comprises at least one of polyacrylate, polyamide, polyimide, polyamideimide, polyvinylidene fluoride, styrene-butadiene rubber, sodium alginate, polyvinyl alcohol, polytetrafluoroethylene, polyacrylonitrile, carboxymethyl cellulose, sodium carboxymethyl cellulose and potassium carboxymethyl cellulose; And / or, the negative electrode active coating further comprises a negative electrode conductive agent, wherein the negative electrode conductive agent comprises carbon black and single-walled carbon nanotubes; preferably, the aspect ratio of the single-walled carbon nanotubes is greater than or equal to 500.

9. The lithium ion secondary battery according to any one of claims 1 to 4, wherein: The silicon-carbon material comprises a porous carbon matrix and silicon dispersed in the pores of the porous carbon matrix; Preferably, the silicon-carbon material further includes a carbon coating layer located on the surface.

10. The lithium ion secondary battery according to any one of claims 1 to 4, wherein: The porosity of the negative electrode sheet is 10%-60%, preferably 25%-35%; And / or, the surface resistance of the negative electrode sheet is 2Ω·cm-20Ω·cm; preferably 5Ω·cm-15Ω·cm.

Citation Information

Patent Citations

  • Silicon-based negative plate, preparation method thereof and secondary battery

    CN115775866A

  • Negative electrode material, negative electrode plate and battery

    CN116053447A

  • Secondary battery, preparation method thereof and electric device

    CN116364860A

  • Battery and device

    CN118712335A

  • Silicon-carbon composite material, preparation method thereof, negative pole piece and lithium ion battery

    CN118867145A